(untitled) (IAHS Medical Journal, 2022)
Background : Transcutaneous Electrical Nerve Stimulation (TENS) is often used to treat Low-Back Pain (LBP). However, its effectiveness is controversial in non-specific chronic LBP (CLBP). The study aimed to determine TENS’ efficacy in treating non-specific CLBP when added to Non-Steroidal Anti- Inflammatory Drugs (NSAIDs) and Activities of Daily Living (ADL). Materials and methods: This randomized controlled clinical trial was conducted in the Department of Physical Medicine and Rehabilitation of Chittagong Medical College Hospital, Chattogram, over six months from January 2019 to June 2019. Ninety patients suffering from LBP for more than six weeks were enrolled and randomized into Group A, and Group B. Patients in both groups were treated with NSAID+ADL. TENS was added to the patients of Group B. Subjective pain intensity score, Visual Analogue Scale (VAS) Tenderness index, Disability due to pain, Spinal mobility index and Oswestry Disability Index was the outcome parameters assessed at baseline and after eight weeks of intervention. Results: Ten patients were lost to follow-up (Five from each group) giving an effective sample of 80 (40 in each group). Both the groups were similar at enrollment in terms of the demographic, clinical and laboratory parameters. In Group A and B, the VAS score at baseline was 7.06±0.81 and 7.11±0.83, respectively. At eight weeks, the VAS score was 6.55±0.77 and 6.11±0.75, respectively, in Group A and B. Reduction of VAS scores was significant in both groups without any statistical differences. Similarly, Disability due to pain and Oswestry Disability Index scores reduced significantly from baseline to eight weeks after treatment in both groups, without statistically significant differences. Conclusion: The study ascertained no additional benefit of TENS in patients of non specific CLBP when added to NSAID and ADL. IAHS Medical Journal Vol 5(1), June 2022; 82-86